2019
DOI: 10.1017/s0007114519000229
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary phytochemical index and mental health in women: a cross-sectional study

Abstract: Previous studies have shown that unhealthy dietary patterns are among the most important modifiable risk factors in the development of mental health disorders. We examined the association of dietary phytochemical index (DPI) with symptoms of depression, anxiety and psychological distress in Iranian women. In this cross-sectional study, a total of 488 women aged 20–50 years old attending health centres in the south of Tehran in 2018 were included. A validated and reliable FFQ was used for dietary assessment. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…[ 18 ] Previous reports investigated the DPI-disease risk and an inverse relationship between DPI and obesity, oxidative stress, hypercholesterolemia, insulin resistance, prediabetes and hypertension was reported. [ 14 ] In addition, a decrease in oxidative stress together with high DPI was also found by Vincent et al[ 24 ] In the current study, a moderate positive correlation was observed between DPI and TAS in the control group, while there was no significant correlation between DPI and oxidative biomarkers in the patient group. Disease-related effects and/or dietary factors on oxidative biomarkers may have caused the absence of such a correlation in the patient group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[ 18 ] Previous reports investigated the DPI-disease risk and an inverse relationship between DPI and obesity, oxidative stress, hypercholesterolemia, insulin resistance, prediabetes and hypertension was reported. [ 14 ] In addition, a decrease in oxidative stress together with high DPI was also found by Vincent et al[ 24 ] In the current study, a moderate positive correlation was observed between DPI and TAS in the control group, while there was no significant correlation between DPI and oxidative biomarkers in the patient group. Disease-related effects and/or dietary factors on oxidative biomarkers may have caused the absence of such a correlation in the patient group.…”
Section: Discussionsupporting
confidence: 83%
“…Phytochemicals are known as plant-derived bioactive substances including phenolic parts (e.g., phenolic acids, flavonoids, lignans, tyrosol esters), organosulphur compounds, and isoprenoids. [ 14 , 15 ] Phytochemicals are found in vegetables, fruits, whole grains, legumes and nuts and in other plant-based foods. They modify and reduce oxidative stress and inflammation and, thus, protect organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, an Italian study reported that dietary intake of phenolic acid (OR = 0.64, 95% CI: 0.44, 0.93), flavanones (OR = 0.54, 95% CI: 0.32, 0.91), and anthocyanins (OR = 0.61, 95% CI: 0.42, 0.89) showed significant inverse associations with depressive symptoms in 1572 adult Southern Italian dwellers in a dose-response manner [139]. In a cross-sectional study published in 2019, higher dietary phytochemical intake was reported to be associated with lower prevalence of depressive symptoms in a total of 488 female participants (OR 0.22; 95% CI 0.12, 0.38) [140]. Antioxidants may improve depressive symptoms, even in a one-time administration.…”
Section: Nutrients and Depression: Focusing On Dietary Antioxidantsmentioning
confidence: 99%
“…In addition, an inverse association between subclass flavonoid (flavonol, flavone, and flavoanone) intake and depression risk has also been reported in a cohort study of middle-aged and older females in the United States [ 13 ]. A cross-sectional study showed that the highest dietary phytochemical index group had a lower prevalence of depressive symptoms among females in Iran [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individual compounds from flavonoids and carotenoids have been tested for mechanisms in important drug targets, MAO (MAOA and MAOB) and BDNF [ 15 , 50 , 60 , 61 , 62 , 63 ], which are known to be associated with depression through molecular docking studies for possible inhibitory roles. In flavonoids, MAO inhibition was selected to study the mechanism of anti-depression as some flavonoids are known to inhibit the MAO enzyme in the literature [ 57 , 59 , 61 ]. However, the docking score of the selected flavonoids had positive correlations in MAOA and MAOB, which is in line with the literature suggesting that a similar binding pocket is present in both these targets [ 64 ].…”
Section: Discussionmentioning
confidence: 99%